Possibilities of laboratory and field testing in ski mountaineering - Novák, D. (Mazarykova Universität, 2023)
This thesis examines the relationship between ski mountaineering-specific field tests and laboratory tests, anaerobic and aerobic, in seven national-level competitors. Positive correlations were found between maximum power and average speed and between maximum power and average vertical speed in anaerobic testing. In aerobic testing, strong positive correlations were found between VO2max and average vertical speed in stages 4 and 3. The study highlights the potential of field testing to evaluate athlete performance and improve training in competitive ski mountaineering.